1979
DOI: 10.1111/j.1749-6632.1979.tb18738.x
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Among Shipyard Workers in Genoa, Italy

Abstract: The dockyards of Genoa are exposed to many known or suspect carcinogenic agents, namely, asbestos, silica, polycyclic aromatic hydrocarbons, and halogenated hydrocarbons; other possibly harmful substances are trace amounts of aromatic amines, welding smokes, paints, and lipid-removing solvents. A cohort study of causes of death of 2190 dockyard workers in Genoa was conducted between January 1, 1960 and December 31, 1975. Mortality rates were calculated for 20 different occupational categories, for which there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
29
1

Year Published

1985
1985
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(34 citation statements)
references
References 26 publications
4
29
1
Order By: Relevance
“…The demonstration of an increased incidence of lung cancer in several occupational categories at the shipyard is in accordance with the results of other investigations (9,17,18,20,21). However, the results from these studies are inconsistent as to which occupational groups had an excess of asbestos-related cancers, probably due to diverse routines for asbestos handling or possibly to methodological shortcomings.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The demonstration of an increased incidence of lung cancer in several occupational categories at the shipyard is in accordance with the results of other investigations (9,17,18,20,21). However, the results from these studies are inconsistent as to which occupational groups had an excess of asbestos-related cancers, probably due to diverse routines for asbestos handling or possibly to methodological shortcomings.…”
Section: Discussionsupporting
confidence: 81%
“…The magnitude of the excess was higher than that reported in some epidemiologic studies on shipyard employees (9,17,20), while other authors have demonstrated an approximately twofold risk of lung cancer for shipyard workers (19,21,22).…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…Since a similar mortality pattern was found in other metal fume-exposed workers such as molders and coremakers, Coggon et al concluded that the primary causative agent could be the metallic fume components or possibly O 3 or NO. Studies from the US associating increased mortality from pneumonia due to welding fume exposure are few, but most support an increased risk in welders of pneumonias other than bronchopneumonia (Puntoni et al, 1979;Beaumont and Weiss, 1980;Polednak, 1981;McMillan and Pethybridge, 1983;Milham, 1983;Newhouse et al, 1985).…”
Section: Human Immunotoxicity Studiesmentioning
confidence: 99%
“…besides several completed occupational studies (2,5,6,7,10,13,18,22,23,24,26,27), other investigations are under way (19) concerning shipyard workers with correspondingly high cohort figures 2 (Finland, England), as well as concerning arc welders exposed to nickel and chromium fumes (US) but not exposed to asbestos, as can be expected in shipyards. In the meantime, a protocol has been worked out by the World Health Organization (Regional Office for Europe) which is recommended as a basis for planning future prospective studies.…”
Section: Discussionmentioning
confidence: 99%